Moving Mountains : Ethnicity and Livelihoods in Highland China, Vietnam, and Laos - Forsyth, Tim; Michaud, Jean (Book collections on Project MUSE., 2011)
This collection argues that minorities in the Southeast Asian Massif are not powerless in the face of economic and political change in the region - they are drawing on ethnicity and culture to indigenize modernity and maintain their livelihoods.